Idiopathic Subareolar Breast Abscess in a Male Patient - Aiyappan, Senthil Kumar (J Clin Diagn Res, 2015)
We present a case of left breast abscess in a young male patient who presented with acute onset swelling left breast. Imaging studies helped in accurate diagnosis and the case was managed by subareolar incision and drainage. Subareolar breast abscess is an uncommon entity in male and should be kept as a differential diagnosis for male breast swellings.